Surveillance and Patrolling of Women Safety Using Visual Trigger Automation - J. Nithyashri, Brindha D., S. Balakrishnan, S. Vinodhkumar (Mathematical Statistician and Engineering Applications, 2022)
Patrol and security both rely on surveillance. The majority of the work involves spending a lot of time watching out for bad things to happen. This is a rather boring chore, but it is one that we must complete. Before we develop convoluted hypotheses, let's consider how surveillance functions naturally. When we see something out of the ordinary when watching a video broadcast, we act. In essence, our technology should scrutinise each frame of the video in an effort to find something out of the ordinary. Does this procedure sound familiar? Our idea is to trigger a notification to the nearby control room when some violence carried over against women is detected. The CCTV camera will be connected to the server where the processing of Video frames takes place, once a violence or similar activities is detected it will notify the control room in a seamless and effective manner. Our solution is divided into two parts, CCTV Surveillance automation and Intelligent Mobile application for Women.